Femtosecond light pulse response of photodetectors based on Graphene/n-Si heterojunctions. (November 2019) - Scagliotti, M.; Salvato, M.; De Crescenzi, M.; Kovalchuk, N.G.; Komissarov, I.V.; Prischepa, S.L.; Catone, D.; Di Mario, L.; Boscardin, M.; Crivellari, M.; Castrucci, P.
Abstract: To take advantage of the graphene appealing electronic properties, in this work we present a photodetector (PD) based on graphene/n-silicon heterojunction (GSH). In this device, graphene acts as light transmitter, counter electrode junction element and photocarrier collector. The photodetector has been provided with metal contacts allowing either photovoltaic or photoconductive operation mode. We investigated the response of GSH PD to a 35-femtosecond laser pulse. In the photovoltaic configuration, the PD exhibits rise times of some tens of nanoseconds, detecting light from ultraviolet (275 nm) to infrared (1150 nm). In photoconductive mode applying a gate voltage V G, the external quantum efficiency hugely increases, from a value of 2% up to 200%. Together with the observation of a rise time, that decreases down to a minimum value of about 1 ns, this makes our device even more competitive and comparable with commercial photodetectors. Graphical abstract: Image 10140